Dilemma: Organic Growth or Acquisition? A Greek Bank Crosses The Borders and Goes International. Two Case Studies: Acquisition in Serbia and Organic Growth in Albania. Compare and Construct - Papaioannou, Georgia (2008)
This paper intends to compare and contrast the strategy of organic growth against the one of acquisition in the case of a bank which decides to cross the borders and expand to foreign countries. In order to analyse this dilemma this study will examine which are the most important variables when an acquisition is under consideration, which are the factors that lead to the choice of organic growth, despite the fact that organic growth is most of the times translated into a slower paced growth and what is the role of the macroeconomic environment and the influence of the regulatory framework of each country. Furthermore, this paper discusses which are the most important data that a bank should take into account in order to make that decision and under which circumstances it is worth to take the chance to proceed to an acquisition or insist on organic growth. For that cause we will examine the case of Alpha Bank, which is a Greek bank and has faced this dilemma during its expansion to South East Europe.